JAPANESE MODEL OF CITIZEN PARTICIPATION IN PUBLIC SAFETY: LEGAL AND PHILOSOPHICAL FOUNDATIONS, EVOLUTION, AND COMPARATIVE ANALYSIS - Urazbaev Abatbay Askerbaevich (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
The Japanese model of citizen engagement in maintaining public order represents a unique synthesis of historical traditions, evolutionary adaptation, and the philosophy of "wa" (harmony), believed to contribute to low crime rates and high trust in the police. Rooted in the Tokugawa-era go’nin-gumi system and developed through tonari-gumi and the Koban network, it exhibits resilience supported by decentralization and collective responsibility. Employing a mixed-method approach, this study traces its development from the 17th century to 2021, drawing on data from the National Police Agency and legal frameworks such as the Local Autonomy Law (1947). Comparative analysis with China, the United States, and the Republic of Korea highlights its strengths in preventing petty crime and fostering social capital. The philosophy of "wa" may enhance trust, contrasting with coercion in China and pragmatism in the Republic of Korea. However, its success is context-dependent, limiting direct adaptation in individualistic societies like the United States. This study underscores the model’s potential for collectivist nations and suggests further exploration of its applicability amid globalization, balancing tradition and innovation.